The Optimal Cost Estimating for Improvement of Product Design - Lee, Hongchul; Lee, Jaemyung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
<span style="font-size: 10pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Microsoft JhengHei’; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">While the concepts of design for manufacturability and concurrent engineering have made significant advances in integrating the design function with other areas in companies, major gaps remain in the timely and accurate provision of costing information to designers. Inappropriate design could increase the redesign cost and delay the product realization. This present 3-step research aims to reduce the design cost of the product. The first step sets up the optimal cost, which is the engineering target based on the function. The second step estimates the current function cost according to the unit through the function and quantitative analysis for the basic model<span style="font-size: 10pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’맑은 고딕’; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">.<span style="font-size: 10pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Microsoft JhengHei’; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US"> In the third step, the design of a unit is reviewed according to the priority of the difference between the optimal cost and the function cost. Arranging the unit design parameters, the best design option is set up according to the level.